Fig. 2 in Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica - Kuzmina, T. A.; Dykyy, I. V.; Salganskij, O. O.; Lisitsyna, O. I.; Korol, E. M.; Kuzmin, Yu. I. (Zenodo, 2021)
Fig. 2. Intensity of teleost fish infection off the area of the UAS "Akademik Vernadsky" by five parasite taxa (proportion of different parasite taxa is in %). Published as part of Kuzmina, T. A., Dykyy, I. V., Salganskij, O. O., Lisitsyna, O. I., Korol, E. M. & Kuzmin, Yu. I., 2021, Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica, pp. 251-264 in Zoodiversity 55 (3) on page 257, DOI:10.15407/zoo2021.03.251, http://zenodo.org/record/6455979